Analysis of Students’ Mathematical Reasoning Ability in Solving Problems on Quadratic Equations at SMP Negeri Bitefa - Hendrika Bete; Aprilia Binsasi; Maria Naimnule (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2026)
This study aimed to analyze students’ mathematical reasoning ability in solving problems on the topic of quadratic equations at SMP Negeri Bitefa. The research used a qualitative descriptive approach with 18 eighth-grade students as participants. Data were collected through tests of mathematical reasoning and follow-up interviews with three selected subjects representing high, medium, and low levels of reasoning ability. The results showed that students’ reasoning abilities varied across five indicators: (1) making initial conjectures and predictions based on problem context, (2) performing mathematical manipulations to find patterns and relationships, (3) constructing systematic mathematical arguments and proofs, (4) evaluating mathematical arguments for accuracy, and (5) integrating analysis results to draw logical conclusions. The findings revealed that students generally demonstrated moderate reasoning ability. The strongest performance appeared in the ability to draw conclusions (50.74%), while the weakest was in generating conjectures (44.81%). These results suggest the need for mathematics instruction that emphasizes inquiry-based and problem-solving learning strategies to improve reasoning competence.